Effect of Phenophased irrigation on Vegetable Cowpea (Vigna sesquipedalis) under graded doses of nitrogen and phosphorus - Jyothi K.I (Department of Agronomy, College of Agriculture, 1995)
An experiment was conducted at the Instructional Farm attached to the college of Agriculture, Vellayani in the summer rice fallows during 1933 to study the effect of phenophased irrigation on vegetable cowpea cv. Malika under graded doses of nitrogen and phosphorus. The trial was laid out as a 5 x 3 factorial experiment in randomised block design with 3 replications. The treatments comprised of five irrigation treatments and three ratios of N and P. The study revealed that the crop responded to irrigation and application of N and P at the ratio of 30 and 45 kg ha-1. Biometric characters viz. plant height, number of leaves per plant, LAI, total DMP and CGR and yield attributing characters viz. number of pods per plant, length of the pods and number of seeds per pod were favourably influenced by maintaining a moisture regime of 75 per cent of field capacity throughout the crop growth period. The maximum LAI, total DMP, CGR and yield attributes viz. number of pods per plant, length of the pods and number of seeds per pod were significantly increased upto an NP ratio of 30:45 kg ha-1. Irrigation treatments could not produce any marked difference in green pod yield mainly due to the frequent rainfall received during the harvesting period of one and a half months. Unlike pod yield, haulm yield was appreciably influenced by irrigation and the maximum haulm yield was noticed by irrigating the crop at 75 per cent of field capacity throughout the crop growth period. The maximum yield of green pods and haulm were noticed at an NP ratio of 30:45 kg ha-1. The uptake of major nutrients viz. N, P and K by the crop and the quality parameters (protein content of pods) significantly increased by irrigation at 75 per cent of field capacity throughout the crop growth period and at the NP ratio of 30:45 kg ha-1. The field water-use efficiency was higher in less frequently irrigated plots and at an NP ratio of 30:45kg ha-1. Soil moisture-extraction pattern showed that on an average, the crop extracted 67.29, 23.05 and 9.66 per cent of moisture from 0-15, 15-30 and 30-45 cm soil depths respectively. Drier regimes and an increase in NP ratio showed a tendency to extract more moisture from deeper layers. The yield response factor indicated a marginal response of the crop to moisture stress at the flowering stage. Available N, P and K contents of the soil after the experiment indicated a decrease in soil nutrient status with an increase in the number of irrigations. The results of economic analysis revealed that net income and benefit cost ratio increased by irrigating the crop at 75 per cent of field capacity throughout the crop growth period and at the NP ratio of 30:45 kg ha-1.